Respostas
respondido por:
0
x² - x - 6 = 0
Fatorando:
(x - 3)(x + 2)
x - 3 = 0 ---> x' = 3
x + 2 = 0 ---> x'' = - 2
S = {-2 ; 3}
Fatorando:
(x - 3)(x + 2)
x - 3 = 0 ---> x' = 3
x + 2 = 0 ---> x'' = - 2
S = {-2 ; 3}
respondido por:
1
x² - x - 6 = 0
a = 1; b = - 1; c = - 6
Δ = b² - 4ac
Δ = (-1)² - 4.1.(-6)
Δ = 1 + 24
Δ = 25
a = 1; b = - 1; c = - 6
x = - b +/- √Δ = - ( - 1) +/- √25
-------------- ----------------------
2a 2.1
x' = 1 + 5
---------- = 6/2 = 3
2
x" = 1 - 5
-------- = - 4/2 = - 2
2
R.: x' = 3 e x" = - 2
a = 1; b = - 1; c = - 6
Δ = b² - 4ac
Δ = (-1)² - 4.1.(-6)
Δ = 1 + 24
Δ = 25
a = 1; b = - 1; c = - 6
x = - b +/- √Δ = - ( - 1) +/- √25
-------------- ----------------------
2a 2.1
x' = 1 + 5
---------- = 6/2 = 3
2
x" = 1 - 5
-------- = - 4/2 = - 2
2
R.: x' = 3 e x" = - 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás